2018
DOI: 10.1200/jco.2018.36.15_suppl.3584
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CD73 expression in resected colorectal cancer liver metastasis.

Abstract: Immune checkpoint blockade has not yet been effective in patients with mismatch repair proficient metastatic colorectal cancer. Targeting immunosuppressive metabolic pathways is being explored as a new immunotherapeutic approach. We assessed whether CD73, the rate limiting enzyme that catalyzes the degradation of extracellular AMP into immunosuppressive adenosine, could be an immunological determinant of colorectal liver metastases (CRLMs). By immunofluorescence on tissue microarrays, intratumoral CD73 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
8
2
Order By: Relevance
“…Liver metastasis occurs in 50% CRC patients (237). Recently, studies have shown high CD73 expression associates with significantly shorter time to recurrence and poor survival (238). In renal cancer patients, an adenosine high (AdenoSig hi ) expression signature was identified in pretreatment biopsies and associated with clinical response to A2AR antagonism (124).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Liver metastasis occurs in 50% CRC patients (237). Recently, studies have shown high CD73 expression associates with significantly shorter time to recurrence and poor survival (238). In renal cancer patients, an adenosine high (AdenoSig hi ) expression signature was identified in pretreatment biopsies and associated with clinical response to A2AR antagonism (124).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Furthermore, both enzymes regulate the magnitude of the purinergic reaction surrounding the immune cells. High expression of CD73 is therefore associated with low levels of lymphocytes in the TME and poor prognosis in for example colorectal, prostate, and triple-negative breast cancer [44][45][46][47]. Of note, CD73 is regulated by HIF-1alpha and therefore more abundant in a hypoxic microenvironment [48].…”
Section: Main Molecular and Immunological Features Of Icdmentioning
confidence: 99%
“…35,36 Previous clinical studies have reported the possibilities of increased CD73 expression in gastric, liver, pancreatic, and colorectal cancers, as biomarkers for poor prognosis and malignancy. 15,20 In this study, we demonstrated for the first time that extracellular adenosine can directly upregulate PD-L1 expression in human macrophages. The immunosuppressive adenosine was potentially produced by the ectoenzymes CD39 and CD73, and accordingly, the CD73 inhibitor AB680 significantly reduced PD-L1 levels in both human macrophages and TAMs obtained from mouse models of CRC.…”
Section: Discussionmentioning
confidence: 62%